Memahami peran inflasi dalam krisis ekonomi: Dampaknya terhadap investasi dan strategi menghadapi pasar finansial - Fitriya, Lailatul; Bachtiar, Mochammad Fadly (Maliki Interdisciplinary Journal, 2024)
This article discusses the role that inflation plays in the context of an economic crisis and how it has a major impact on investments and the tactics used to deal with financial markets. Inflation, which is a major indicator of economic dynamics, is often a factor that causes instability during times of crisis. This article highlights the close relationship between inflation and economic crises, examines its impact on various types of investments, and analyzes strategies that can be adopted to manage financial markets in times of economic uncertainty. By understanding this connection more deeply, it is hoped that readers can gain a broader understanding to make smarter and more adaptive investment decisions when facing economic challenges in the future.